Application Of Internet Of Things (Iot) On Controlled Vertical Agriculture - Rasidi, Nazirul Asyraff (Universiti Sains Malaysia, 2019)
Nowadays, more sensors being integrated together in a network in many places such as home appliances including climate control, security camera system and automobiles. All of these systems give lot of benefits to the people which will help lives easier, however the majority of these automation/control systems in garden and home scenarios are either expensive, difficult to implement or all of those reasons. The Node MCU is an open source IoT platforms which includes firmware that runs on ESP8266 Wi-Fi SoC and only require a small amount of electrical power. The Node MCU equipped with GPIO interface pins which allow to have different inputs or outputs assigned to the board to handle various type of functions such as communicating with the sensors or turning on a circuit. Using Node MCU devices, a project has been developed with an affordable wireless sensor network in greenhouse system that communicates with a central server where the sensor data is collected. The sensor data will be sent to the mobile application to help people be easily monitor the sensors through the mobile application and will reduce the amount of human effort required in farming. The mobile application will allow the people to monitor the humidity and temperature inside the greenhouse. Besides that, people also can control the lightening and watering system of the greenhouse by using the mobile application. The ventilation also can be controlled by switching on or off the fan inside the greenhouse. This open source projects allows other interested people to develop the system further to expand the functionality and future possibilities of the system.